Additions to the checklist of the bee species of Slovenia (Hymenoptera: Apoidea) - Gogala, Andrej (Acta entomologica slovenica (Ljubljana), 2003)
6 bee species new to the fauna of Slovenia were found by the authors since thepublication of the Checklist. Two additional species, recorded for Sloveniaby others in the meantime, are also listed. One species has to be omitted from the list. With this, the number of known bee species in Slovenia is 543.
Keywords: čebele; entomologija; favna; Hymenoptera; Slovenia; Slovenija